2021
DOI: 10.1108/ijoem-09-2020-1087
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and consequences of consumers' attitudes toward product placements: evidence from India

Abstract: PurposeAdvertising clutter has fueled the rise of nontraditional advertising methods. The current study, conducted in India, adopted the consumer socialization framework to assess product placement attitudes and behaviors.Design/methodology/approachA questionnaire-based survey was conducted to gauge consumers' responses to product placements. Structural equation modeling (SEM) was applied to analyze the relationship between different variables.FindingsThe results revealed that young Indian adults are positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 77 publications
(146 reference statements)
0
4
0
Order By: Relevance
“…The overall results of the study of Davtyan and Cunningham (2017) clearly demonstrate a positive impact of TV commercials on purchase intention in terms of both brands, "Heinz" and "Snapple" that were used in their experiment. In addition to that, one of the Indian studies emphasizes that product placements are well-liked by young adults in India because they assume that including brands in content improves the authenticity of a product image (Kaur et al, 2021). Contradictory to most existing literature, the current authors hypothesize that TV commercials are likely to evoke a higher purchase intention in consumers than product placements.…”
Section: Hypotheses Developmentmentioning
confidence: 89%
“…The overall results of the study of Davtyan and Cunningham (2017) clearly demonstrate a positive impact of TV commercials on purchase intention in terms of both brands, "Heinz" and "Snapple" that were used in their experiment. In addition to that, one of the Indian studies emphasizes that product placements are well-liked by young adults in India because they assume that including brands in content improves the authenticity of a product image (Kaur et al, 2021). Contradictory to most existing literature, the current authors hypothesize that TV commercials are likely to evoke a higher purchase intention in consumers than product placements.…”
Section: Hypotheses Developmentmentioning
confidence: 89%
“…Positive brand attitudes are generated when product placements are consistent with the contents plot and the affective tones it evoked (Gillespie et al, 2018). Product placements are viewed positively by consumers, who believe that including brands in content improves the authenticity of the online video (Kaur et al, 2021). Product placement is used to create brand awareness, raise the brand image, increase public relations and generate a plot for a new product launch (Russell and Belch, 2005).…”
Section: Product Placementmentioning
confidence: 99%
“…Chinchanachokchai and Gregorio (2020) adopt consumer socialization as the conceptual framework and point out that different socialization agents (peers and media) have differing effects on SMP advertising attitudes, which mediate SMP ad avoidance. Kaur et al (2021) use consumer socialization as the guiding framework to investigate product placement effectiveness through purchase intention and find that socialization agents have a significantly influence on viewers' attitudes toward product placements which in turn influence their purchase intentions. In general, studies have found that customer organization socialization has effects on customer behavior and emotion (Kelley et al, 1992;Cooper-Thomas and Anderson, 2006); however, its effects on employee behaviors and emotion in an interactive service process have not been fully discussed.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%